2016
DOI: 10.1088/2053-1583/4/1/011006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the second- and third-order nonlinear optical susceptibilities of monolayer MoS 2 using multiphoton microscopy

Abstract: Characterization of the second-and third-order nonlinear optical susceptibilities of monolayer MoS 2 ... Supplementary Information forCharacterization of the second-and third-order nonlinear optical susceptibilities of monolayer MoS 2 using multiphoton microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
114
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 42 publications
(90 reference statements)
15
114
4
Order By: Relevance
“…The angle dependence of THG is totally different to SHG. For the monolayer TMDs with D 3 h space group, the polarization of THG signal is always same with the excitation polarization, independent on the orientation of the monolayer crystal (Figure F) . Another important point is that THG would vanish under circularly polarized light (CPL) excitation .…”
Section: Nlo Processes In Tmdsmentioning
confidence: 93%
See 3 more Smart Citations
“…The angle dependence of THG is totally different to SHG. For the monolayer TMDs with D 3 h space group, the polarization of THG signal is always same with the excitation polarization, independent on the orientation of the monolayer crystal (Figure F) . Another important point is that THG would vanish under circularly polarized light (CPL) excitation .…”
Section: Nlo Processes In Tmdsmentioning
confidence: 93%
“…SHG of the bulk MoS 2 is very weak and χ (2) is around 10 −14 m/V; however, three groups simultaneously reported that SHG of monolayer MoS 2 , WS 2 , and WSe 2 increased dramatically . Later, numerous SHG studies were conducted on MoS 2 , WS 2 , WSe 2 , MoSe 2 , and MoTe 2 , and χ (2) was reported on the order of magnitude of 1 nm/V, which is much higher than the most used commercial nonlinear crystals (eg, χ (2) of BBO, KTP, and LiNbO 3 are on the order of magnitude of pm/V). The large nonlinear susceptibility of monolayer compared with bulk is ascribed to the inversion symmetry breaking.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different non-linear optical phenomena like second-, third-harmonic generation and four wave mixing (FWM) [5][6][7] can be quite strong in these materials [8][9][10][11][12][13][14][15]. However, the interpretation of the nonlinear optical response is strongly affected by electronic and phonon resonances [16][17][18][19], therefore the knowledge of the interplay between these resonances is desirable.…”
mentioning
confidence: 99%